What do we know about the second moment of financial markets? - Grobys, Klaus (Elsevier, 2021)
Recent research shows that the vast majority of scientific studies published in leading finance journals fails scientific replication (Hou, Xue, and Zhang, 2020; Harvey, Liu, and Zhu; 2016). This study argues that p-hacking, publication pressure and the selection bias from leading finance journals are perhaps not the underlying root cause for this issue. This study shows that standard methodologies often used in finance research are inevitably sample-specific due to the very nature of financial markets. While the consensus of earlier research postulates a rejection of the time-honored Levy hypothesis, the results of this study strongly indicate that the variance of variance does not exist in any of the financial key markets that are considered. An unexpected finding of this study is that the variance process governing the U.S. dollar foreign exchange rate market is generating more extreme events than the Bitcoin market. The results cast doubts on the validity of methodologies currently used in finance research.
Keywords: Finance; Pareto distributions; Power laws; Second moment; Variance; Variance of variance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|